Nano-enzyme-based high-compatibility non-invasive semi-dry flexible electrode and preparation method thereof

Through the highly compatible semi-dry flexible electrode combined with nanoenzyme hydrogel material and PEDOT:PSS, etc., the problem of insufficient oxidation resistance and biocompatibility of existing semi-dry electrodes is solved, and low contact impedance and long-term stability are achieved , suitable for monitoring EEG signal.

CN119138903APending Publication Date: 2024-12-17TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411250836.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing semi-dry electrodes lack antioxidant properties and biocompatibility when contacting the skin, resulting in signal distortion and health risks, and are complex in installation and difficult to use for a long time.

Method used

Using nanoenzyme hydrogel material, a highly compatible non-invasive semi-dry flexible electrode is formed by soaking silver chloride electrode in a specific solution and combining it with PEDOT:PSS, polyacrylamide and other materials, and combining it with ultraviolet curing technology. , electrodes with low electrode-skin contact impedance and strong oxidation resistance were prepared.

Benefits of technology

It achieves low electrode-skin contact impedance, oxidation resistance and biocompatibility, ensuring the stability and safety of the electrode during long-term use, and is suitable for EEG signal monitoring, which is significantly better than traditional electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119138903A_ABST
    Figure CN119138903A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-enzyme-based high-compatibility non-invasive semi-dry flexible electrode and a preparation method thereof. The preparation method comprises the following steps: treating a conductive part of a universal silver chloride disc-shaped electrode for an electroencephalograph; (2) soaking the conductive part of the treated universal silver chloride discoid electrode for the electroencephalograph in a silane aqueous solution; taking out, cleaning and drying; (3) preparing a prepolymer solution of the nano-enzyme hydrogel; (4) arranging the conductive part of the electrode obtained in the step (2) in a mold with a notch in the side wall, and arranging the insulated wire part of the electrode outside the mold in a manner that the insulated wire part penetrates through the notch; casting the prepolymer solution of the nano-enzyme hydrogel into a mold, irradiating with an ultraviolet lamp, and standing; the high-compatibility non-intrusive semi-dry flexible electrode based on the nano-enzyme is obtained after the mold is removed, the electrode has low electrode-skin contact resistance and high robustness, and the nano-enzyme hydrogel has low electrode-skin contact resistance and can be repeatedly used for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biosensors, and in particular relates to a highly compatible non-invasive semi-dry flexible electrode based on nanozymes. Background Art

[0002] Non-invasive brain-computer interfaces have shown great potential in many application fields such as sleep monitoring, fatigue detection, and neurofeedback training. Compared with invasive brain-computer interfaces, non-invasive brain-computer interfaces do not introduce health risks, so they have received widespread attention. The electroencephalogram electrodes commonly used in traditional non-invasive brain-computer interfaces are mainly divided into two types: dry electrodes and wet electrodes. Dry electrodes are made of solid conductive materials (such as metal, conductive silicone, and conductive polymers). Although they are easy to install, they have a high contact impedance with the skin, are sensitive to motion artifacts, and can easily cause signal distortion during movement.

[0003] Wet electrodes use materials such as silver / silver chloride (Ag / AgCl) and conductive paste, which have the advantages of low polarization and stable potential, but the conductive paste involved cannot be formed, the installation process is complicated, and it may cause short circuit problems in dense electrode layouts. In view of the limitations of dry electrodes and wet electrodes, scholars have proposed the concept of semi-dry electrodes, which establish stable electrode-skin ion channels through inherent electrolyte solutions, combining the high signal quality of wet electrodes and the ease of use of dry electrodes.

[0004] Existing semi-dry electrodes have no antioxidant properties and low biological activity when in contact with the skin. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a highly compatible non-invasive semi-dry flexible electrode based on nanozymes with strong antioxidant properties and biocompatibility.

[0006] The second object of the present invention is to provide a method for preparing a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0007] The technical solution of the present invention is summarized as follows:

[0008] A method for preparing a highly compatible non-invasive semi-dry flexible electrode based on nanozymes comprises the following steps:

[0009] 1) Mixing a 5-10M hydrogen peroxide aqueous solution and a 98% concentrated sulfuric acid in a volume ratio of 3:5-8 in a container to obtain a mixed solution; immersing the conductive part of a universal silver chloride disc electrode of an electroencephalograph in the mixed solution for 10-20 minutes, preferably 15 minutes, taking it out, and washing it with deionized water;

[0010] 2) soaking the conductive part of the universal silver chloride disc electrode of the electroencephalograph treated in step (1) in a silane aqueous solution for 6-8 hours, preferably 7 hours; taking it out, washing it with deionized water and anhydrous ethanol in turn, and drying it in a nitrogen atmosphere for 2-5 hours, preferably 3 hours; the silane aqueous solution is composed of 25%-30% 3-(isobutyleneoxy)propyltrimethoxysilane (abbreviated as TMSPMA), 2%-4% acetic acid, and the balance is deionized water by volume;

[0011] 3) Prepare the prepolymer solution of nanozyme hydrogel: Add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 M1 nanozyme and glycerol are stirred evenly at a speed of 500-2000 rpm, preferably 1000 rpm, and ultrasonically degassed for 5-10 min, preferably 7 min, MBAA, APS and TEMED are added, and stirred at a speed of 500-2000 rpm for 1-2 min, preferably 1.5 min, and the entire step 3) is protected from light to obtain a prepolymer solution of nanozyme hydrogel;

[0012] The PEDOT:PSS is the abbreviation of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid;

[0013] MBAA is the abbreviation of N,N'-methylenebisacrylamide;

[0014] The APS is the abbreviation of ammonium persulfate;

[0015] The TEMED is the abbreviation of tetramethylethylenediamine;

[0016] The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 8%-20%; 1%-5%; 5%-25%; 0.05%-0.2%; 5%-15%; 0.01%-0.02%; 0.04%-0.2%; 0.1%-1%; deionized water is the balance;

[0017] 4) Casting and curing: The conductive part of the electrode obtained in step 2) is arranged inside a mold with a notch on the side wall, and the insulated wire part of the electrode is passed through the notch and arranged outside the mold; the prepolymer solution of the nanozyme hydrogel obtained in step 3) is cast in the mold, and the ultraviolet light radiation intensity is 50-100 μW / cm 2 Irradiate for 15-60 minutes, preferably 30 minutes, and let stand for 12-48 hours, preferably 24 hours; remove the mold to obtain a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0018] Polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are preferably: 12%, 2%, 10%, 0.05%, 10%, 0.017%, 0.043%; 0.6%; deionized water is the balance.

[0019] The above preparation method prepares a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0020] Advantages of the present invention:

[0021] (1) The electrode of the present invention has low electrode-skin contact impedance and high robustness: The hydrogel in the electrode structure of the present invention has low electrode-skin contact impedance and can be used for a long time and repeatedly. The contact impedance is as low as 2-10 kΩ, which is close to that of a wet electrode, but after 10 hours, the contact impedance is much lower than the latter and more stable.

[0022] (2) Strong antioxidant and biocompatibility: Au 24 The M1 nanozyme has strong antioxidant activity, CAT-like enzyme activity and strong GPx-like enzyme activity, showing strong overall antioxidant properties. The electrode of the present invention showed no toxicity in the cytotoxicity experiment and effectively alleviated the oxidative stress stimulation of H2O2 and LPS in the cell experiment. Compared with the dry electrode, the electrode of the present invention does not cause indentation on the skin.

[0023] (3) Excellent tensile and compressive resistance: The elongation at break of the coagulated nanozyme hydrogel of the electrode of the present invention reaches 600%, and it can recover to its original shape after being compressed to 99%. Even after 200 repeated compressions, its electrochemical impedance remains stable, ensuring the reliability and comfort of long-term wear.

[0024] (4) Non-invasive and easy to use: The non-invasive design of the electrode of the present invention simplifies the operation process, does not require cumbersome conductive paste steps, provides excellent contact effect, and is particularly suitable for long-term monitoring.

[0025] (5) Reliability confirmed by application: The electrode of the present invention has been evaluated on human volunteers in SSVEP experiments. The results show that the electrode shows a significant high power spectral density peak at the stimulation frequency of 10 Hz in the SSVEP experiment, with similar experimental results as the wet electrode, and the EEG signal monitoring was carried out for up to 12 hours. After 9 hours, the effect was significantly better than the wet electrode that had partially dried up.

[0026] The electrode of the present invention demonstrates significant advantages in accuracy, comfort, high compatibility and ease of operation of bioelectric signals, and provides an efficient and reliable solution for the application of non-invasive bioelectric monitoring equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The morphologies of the strip-shaped nanozyme hydrogel (prepared in Example 4) when folded, pasted, twisted, and stretched are shown.

[0028] Figure 2 This is a data graph of the tensile test of the strip-shaped nanozyme hydrogel (prepared in Example 4) on a tensile testing machine.

[0029] Figure 3 This is a diagram showing the effect of nanozyme hydrogel (prepared in Example 4) and dry electrode compressing pig skin at the same pressure.

[0030] Among them, the front row in the middle picture is nanozyme hydrogel, and the back row is dry electrode.

[0031] Figure 4 This is a data graph of the compression test of cylindrical nanozyme hydrogel (prepared in Example 4) on a tensile testing machine.

[0032] Figure 5 This is a graph showing the electrochemical impedance change at 10 Hz of the cylindrical nanozyme hydrogel (prepared in Example 4) before and after 200 compressions.

[0033] Figure 6 The contact impedance change between the nanozyme hydrogel electrode (prepared in Example 1) and the wet electrode and pig skin at 10 Hz within 9 hours.

[0034] Figure 7 The electrochemical impedance change at 10 Hz of the nanozyme hydrogel electrode (prepared in Example 1) immersed in PBS solution for 20 days.

[0035] Figure 8 It is the power spectral density diagram of the EEG data of the nanozyme hydrogel electrode (prepared in Example 1) and the wet electrode in the SSVEP experiment at a frequency of 10 Hz.

[0036] Fig. 9 The nanozyme hydrogel electrode (prepared in Example 1) and the wet electrode were used to record the EEG signals of normal subjects with their eyes closed within 12 hours.

[0037] Fig.10 The power spectral density diagram of the EEG data of the nanozyme hydrogel electrode (prepared in Example 1) was performed on normal subjects in an SSVEP experiment at a frequency of 10 Hz within 14 days (the nanozyme hydrogel electrode cap was worn on the head model during the non-experimental time to simulate the human brain EEG data monitoring process).

[0038] Fig.11 The ABTS activity test results of the nanozyme hydrogel (prepared in Example 4).

[0039] Fig.12 These are the test results of GPx-like enzyme activity of nanozyme hydrogel (prepared in Example 4).

[0040] Fig.13 These are the test results of CAT-like enzyme activity of nanozyme hydrogel (prepared in Example 4).

[0041] Fig.14 The graph shows the survival rate of HT-22 cells after the nanozyme hydrogel (prepared in Example 4) was immersed in complete culture medium for different time periods.

[0042] Fig.15 The graph shows the cell survival rate after nanozyme hydrogel (prepared in Example 4) was immersed in complete culture medium for different time periods and administered to HT-22 cells exposed to H2O2 to induce oxidative stress.

[0043] Fig.16 The graph shows the cell survival rate after nanozyme hydrogel (prepared in Example 4) was immersed in complete culture medium for different time periods and administered to HT-22 cells exposed to LPS to induce oxidative stress.

[0044] Fig.17 The graph is a graph of actual scalp contact impedance data measured by the nanozyme hydrogel electrode (prepared in Example 1), wet electrode, and dry electrode on the NeurScan EEG experimental system. DETAILED DESCRIPTION

[0045] The present invention is further described below by means of specific examples, which are intended to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0046] The Au used in the present invention 24 The preparation of M1 nanozyme can be found in Chinese patent: 2021112082021, atomic precision cluster enzyme and preparation and its application in nervous system diseases. Wherein M can be Cu or Cd, the present invention uses Cu, and Cd can also be used in the present invention.

[0047] In each embodiment, Au 24 M1 nanozyme is short for nanozyme.

[0048] The polyacrylamide with a relative molecular mass of 71.08 g / mol is used as an example, and polyacrylamide with other molecular weights can also be used in the present invention.

[0049] Universal silver chloride disc electrode for electroencephalogram (commercial product). PEDOT:PSS (commercial product)

[0050] In the following embodiments:

[0051] PEDOT:PSS is the abbreviation of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid;

[0052] MBAA is the abbreviation of N,N'-methylenebisacrylamide;

[0053] APS is the abbreviation for ammonium persulfate;

[0054] TEMED is the abbreviation of tetramethylethylenediamine;

[0055] A highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes is referred to as nanozyme hydrogel electrode.

[0056] Example 1

[0057] A method for preparing a highly compatible non-invasive semi-dry flexible electrode based on nanozymes comprises the following steps:

[0058] (1) mixing an 8M hydrogen peroxide aqueous solution and a 98% concentrated sulfuric acid in a volume ratio of 3:6 in a container to obtain a mixed solution; immersing the conductive part of a universal silver chloride disk electrode of an electroencephalograph in the mixed solution for 15 minutes, taking it out, and washing it with deionized water;

[0059] 2) soaking the conductive part of the electroencephalograph universal silver chloride disc electrode treated in step (1) in a silane aqueous solution for 7 hours; taking it out, washing it with deionized water and anhydrous ethanol in turn, and drying it in a nitrogen atmosphere for 3 hours; the silane aqueous solution is composed of 27% 3-(isobutyleneoxy)propyltrimethoxysilane (TMSPMA), 3% acetic acid, and the balance deionized water by volume;

[0060] 3) Prepare the prepolymer solution of nanozyme hydrogel: Add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 M1 nanozyme (referred to as nanozyme) and glycerol were stirred evenly at a speed of 1000 rpm, ultrasonically degassed for 7 min, MBAA, APS and TEMED were added, and stirred at a speed of 1000 rpm for 1.5 min. The whole step 3) was protected from light to obtain a prepolymer solution of nanozyme hydrogel;

[0061] The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 12%, 2%, 10%, 0.05%, 10%, 0.017%, 0.043%; 0.6%; deionized water is the balance;

[0062] 4) Casting and curing: The conductive part of the electrode obtained in step 2) is arranged inside a mold with a notch on the side wall, and the insulated wire part of the electrode is passed through the notch and arranged outside the mold; the prepolymer solution of the nanozyme hydrogel obtained in step 3) is cast in the mold and heated under a UV lamp with a radiation intensity of 70 μW / cm 2 Irradiate for 30 minutes and let stand for 24 hours; remove the mold to obtain a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0063] Example 2

[0064] A method for preparing a highly compatible non-invasive semi-dry flexible electrode based on nanozymes comprises the following steps:

[0065] 1) Mixing a 5M hydrogen peroxide aqueous solution and a 98% concentrated sulfuric acid in a volume ratio of 3:5 in a container to obtain a mixed solution; immersing the conductive part of a universal silver chloride disc electrode of an electroencephalograph in the mixed solution for 10 minutes, taking it out, and washing it with deionized water;

[0066] 2) soaking the conductive part of the universal silver chloride disc electrode for electroencephalograph treated in step (1) in a silane aqueous solution for 6 hours; taking it out, washing it with deionized water and anhydrous ethanol in turn, and drying it in a nitrogen atmosphere for 2 hours; the silane aqueous solution is composed of 25% 3-(isobutyleneoxy)propyltrimethoxysilane (TMSPMA), 2% acetic acid, and the balance deionized water by volume;

[0067] 3) Prepare the prepolymer solution of nanozyme hydrogel: Add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 M1 nanozyme and glycerol were stirred evenly at a speed of 500 rpm, ultrasonically degassed for 5 min, MBAA, APS and TEMED were added, and stirred at a speed of 500 rpm for 2 min. The whole step 3) was protected from light to obtain a prepolymer solution of nanozyme hydrogel;

[0068] The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 8%; 1%; 5%; 0.05%; 5%; 0.01%; 0.04%; 0.1%; deionized water is the balance;

[0069] 4) Casting and curing: The conductive part of the electrode obtained in step 2) is arranged inside a mold with a notch on the side wall, and the insulated wire part of the electrode is passed through the notch and arranged outside the mold; the prepolymer solution of the nanozyme hydrogel obtained in step 3) is cast in the mold and heated under a UV lamp with a radiation intensity of 50 μW / cm 2Irradiate for 60 minutes and let stand for 12 hours; remove the mold to obtain a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0070] Example 3

[0071] A method for preparing a highly compatible non-invasive semi-dry flexible electrode based on nanozymes comprises the following steps:

[0072] 1) Mixing a 10M hydrogen peroxide aqueous solution and a 98% concentrated sulfuric acid in a volume ratio of 3:8 in a container to obtain a mixed solution; immersing the conductive part of a universal silver chloride disc electrode of an electroencephalograph in the mixed solution for 20 minutes, taking it out, and washing it with deionized water;

[0073] 2) soaking the conductive part of the universal silver chloride disc electrode for electroencephalograph treated in step (1) in a silane aqueous solution for 8 hours; taking it out, washing it with deionized water and anhydrous ethanol in turn, and drying it in a nitrogen atmosphere for 5 hours; the silane aqueous solution is composed of 30% 3-(isobutyleneoxy)propyltrimethoxysilane (TMSPMA), 4% acetic acid, and the balance deionized water by volume;

[0074] 3) Prepare the prepolymer solution of nanozyme hydrogel: Add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 M1 nanozyme and glycerol, adjust the speed to 2000 rpm on a stirring table, stir evenly, ultrasonically degas for 10 min, add MBAA, APS and TEMED, stir at 2000 rpm for 1 min, and protect from light throughout step 3) to obtain a prepolymer solution of nanozyme hydrogel;

[0075] The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 20%; 5%; 25%; 0.2%; 15%; 0.02%; 0.2%; 1%; deionized water is the balance;

[0076] 4) Casting and curing: The conductive part of the electrode obtained in step 2) is arranged inside a mold with a notch on the side wall, and the insulated wire part of the electrode is passed through the notch and arranged outside the mold; the prepolymer solution of the nanozyme hydrogel obtained in step 3) is cast in the mold and heated under a UV lamp with a radiation intensity of 100 μW / cm 2 Irradiate for 15 minutes and let stand for 48 hours; remove the mold to obtain a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

[0077] Example 4

[0078] Preparation of Nanozyme Hydrogel:

[0079] 1) preparing a prepolymer solution of nanozyme hydrogel: same as step (3) of Example 1;

[0080] 2) Casting and curing: The prepolymer solution of the nanozyme hydrogel obtained in step 1) is cast into a mold (which can be of various shapes according to experimental requirements) and heated under a UV lamp with an intensity of 70 μW / cm 2 Irradiate for 30 minutes and let stand for 24 hours; remove the mold to obtain the nanozyme hydrogel.

[0081] Example 5

[0082] Preparation of Nanozyme Hydrogel:

[0083] 1) preparing a prepolymer solution of nanozyme hydrogel: same as step (3) of Example 2;

[0084] 2) Casting and curing: The prepolymer solution of the nanozyme hydrogel obtained in step 1) was cast into a mold and heated under a UV lamp with an intensity of 50 μW / cm 2 Irradiate for 60 minutes and let stand for 12 hours; remove the mold to obtain the nanozyme hydrogel.

[0085] Example 6

[0086] Preparation of Nanozyme Hydrogel:

[0087] 1) preparing a prepolymer solution of nanozyme hydrogel: same as step (3) of Example 3;

[0088] 2) Casting and curing: The prepolymer solution of the nanozyme hydrogel obtained in step 1) was cast into a mold and heated under a UV lamp with an intensity of 100 μW / cm 2 Irradiate for 15 minutes and let stand for 48 hours; remove the mold to obtain the nanozyme hydrogel.

[0089] Experimental Example 1

[0090] Tensile properties test

[0091] The morphology of the long strip nanozyme hydrogel prepared in Example 4 when folded, pasted, twisted and stretched is shown as follows: Figure 1 As shown in the figure, when external force is applied to it, the nanozyme hydrogel itself will not be damaged due to its sufficient elasticity and toughness. In addition, the long strip nanozyme hydrogel is placed on a tensile testing machine, and a 50N sensor is used to stretch the long strip nanozyme hydrogel at a speed of 1mm / s. After processing, a data graph of stress and deformation is obtained, as shown in the figure below. Figure 2 The elongation at break of the long nanozyme hydrogel reached 600%, indicating that it has good tensile resistance and toughness.

[0092] Experimental Example 2

[0093] Compression performance test

[0094] Figure 3 The effect of the nanozyme hydrogel prepared in Example 4 and the dry electrode compressing the pig skin under the same pressure is demonstrated.

[0095] The left picture shows the state of pig skin before compression, the middle picture shows the compression process, the front row of the middle picture is nanozyme hydrogel, the back row is dry electrode, and the right picture shows the state of pig skin after compression for 1 hour. It can be clearly seen in the right picture that the dry electrode leaves obvious indentations after compression, while the nanozyme hydrogel has no obvious marks after compression. This shows that the nanozyme hydrogel has less compression damage to the skin under the same pressure, and is softer and more adaptable.

[0096] The cylindrical nanozyme hydrogel was placed on a tensile testing machine, and a 50N sensor was used to compress the nanozyme hydrogel at a speed of 1mm / s. After processing, a data graph of stress and deformation was obtained, as shown in Figure 4 , the cylindrical nanozyme hydrogel can be compressed to 99% without damage, indicating that it has good tensile resistance and toughness.

[0097] In addition, the changes in electrochemical impedance of the cylindrical nanozyme hydrogel at 10 Hz before and after compression 200 times were tested. Figure 5 ,After multiple compressions, the impedance decreased slightly, which may be that compression enhanced the sustained release of ions in the hydrogel, resulting in lower electrochemical impedance.

[0098] Experimental Example 3

[0099] Comparison of long-term contact impedance between nanozyme hydrogel electrode and wet electrode

[0100] like Figure 6 At 3 hours, the contact impedance between the nanozyme hydrogel electrode (prepared in Example 1) and the wet electrode and the pig skin at 10Hz began to change significantly. At 4-5 hours, the wet electrode contact impedance gradually increased to more than 100kΩ, greatly reducing the accuracy of EEG signal monitoring. The nanozyme hydrogel electrode was relatively stable within 9 hours and was still within 10kΩ, reflecting its long-term monitoring stability of EEG signals.

[0101] Fig.17 The graph is a graph of actual scalp contact impedance data measured by the nanozyme hydrogel electrode (prepared in Example 1), wet electrode, and dry electrode on the NeurScan EEG experimental system.

[0102] also, Figure 7 It was shown that the electrochemical impedance of the nanozyme hydrogel electrode remained almost unchanged after being immersed in PBS solution for 20 days, indicating the stability of its electrochemical performance.

[0103] Experimental Example 4

[0104] Long-term wearing functional test of nanozyme hydrogel electrodes

[0105] Gel electrode flexible adaptation and long-term wearing function test method:

[0106] The subjects wore an electrode cap with nanozyme hydrogel electrodes and performed an SSVEP experiment at the beginning. After that, the subjects' closed-eye EEG signals were recorded every 3 hours, and wet electrodes were used for comparison, for a total of 12 hours. In addition, the subjects were asked to wear the nanozyme hydrogel electrode cap for an SSVEP experiment after the first, third, seventh, and fourteenth day.

[0107] Test result analysis:

[0108] like Figure 8 , the power spectral density analysis results of the nanozyme hydrogel electrode (prepared in Example 1) and the wet electrode when the SSVEP (steady-state visual evoked potential) test was performed with 10Hz frequency stimulation. As can be seen from the figure, both electrodes have obvious peaks at a frequency of 10Hz, indicating that they have a good response to 10Hz visual stimulation. Both electrodes generate signals at integer multiples of the frequency (called frequency doubling or harmonics), which are manifestations of the nonlinear characteristics of the nervous system, especially near 20Hz, 30Hz, and 40Hz, indicating that they have higher signal responsiveness and lower noise levels at these frequency points. The ability to reach a comparable level with the experimental gold standard wet electrode is attributed to the better physical and chemical properties of the nanozyme hydrogel electrode, such as better skin fit and lower contact impedance, thereby improving the quality and stability of the signal.

[0109] In addition, long-term stability functional tests were performed, such as Fig. 9 , compared the recording of eye closure signals of subjects from 0 to 12 hours with the nanozyme hydrogel electrode and the wet electrode, the nanozyme hydrogel electrode performed well overall, that is, the signal recorded after 10 hours was stable, while the wet electrode could hardly record EEG signals normally after 9 hours because the conductive paste dried over time. Fig.10 The power spectral density diagrams are obtained by performing SSVEP experiments on the subjects wearing nanozyme hydrogel electrode caps on days 0, 1, 3, 7, and 14. The results show that an obvious peak appeared at the stimulation frequency of 10 Hz in each experiment, reflecting the good long-term EEG signal monitoring function of the nanozyme hydrogel electrode.

[0110] Overall, the nanozyme hydrogel electrode showed excellent performance in the SSVEP test, and can provide a more comfortable and convenient user experience without sacrificing signal quality. It has sufficient advantages in applications that require high-precision neural signal monitoring, such as brain-computer interfaces and neural function testing, and is an effective alternative to wet electrodes.

[0111] Experimental Example 5

[0112] Enzyme performance test

[0113] In order to verify the enzyme-like performance of the nanozyme hydrogel electrode (prepared in Example 1), ABTS, GPx, and CAT enzyme-like tests were performed. The ABTS kit and GPx kit were both produced by Shanghai Biyuntian Biotechnology Co., Ltd. Both kit test methods ultimately used a microplate reader or a UV-visible spectrophotometer to measure the absorbance of each experimental group and control group at a specific wavelength under different reaction times. The test method was strictly in accordance with the instructions.

[0114] Experimental groups:

[0115] Group 1, Preparation of hydrogel:

[0116] 1) preparing a prepolymer solution of a hydrogel: in a container, add deionized water, polyacrylamide, sodium alginate and glycerol, stir evenly at a speed of 1000 rpm, degas by ultrasonication for 7 minutes, add MBAA, APS and TEMED, stir at a speed of 1000 rpm for 1.5 minutes, and keep the whole step 1) away from light to obtain a prepolymer solution of a hydrogel;

[0117] The mass percentages of the polyacrylamide, sodium alginate, glycerol, MBAA, APS, TEMED and deionized water are: 12%, 2%, 10%, 0.017%, 0.043%; 0.6%; deionized water is the balance;

[0118] 2) Casting and curing: The prepolymer solution of the hydrogel obtained in step 1) is cast into a mold (which can be of various shapes according to experimental requirements) and heated under a UV lamp with an intensity of 70 μW / cm 2 Irradiate for 30 minutes and let stand for 24 hours; remove the mold to obtain the hydrogel.

[0119] Group 2, preparation of hydrogels with PEDOT:PSS:

[0120] 1) preparing a prepolymer solution of a hydrogel with PEDOT:PSS added: in a container, add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS and glycerol, stir evenly at a speed of 1000 rpm, degas by ultrasonication for 7 minutes, add MBAA, APS and TEMED, stir at a speed of 1000 rpm for 1.5 minutes, and keep the whole step 3) away from light to obtain a prepolymer solution of a hydrogel with PEDOT:PSS added;

[0121] The mass percentages of the polyacrylamide, sodium alginate, PEDOT:PSS, glycerol, MBAA, APS, TEMED and deionized water are: 12%, 2%, 10%, 10%, 0.017%, 0.043%; 0.6%; deionized water is the balance;

[0122] 2) Casting and curing: The prepolymer solution of the hydrogel with PEDOT:PSS obtained in step 1) was cast into a mold and heated under a UV lamp with an intensity of 70 μW / cm 2 Irradiate for 30 minutes and let stand for 24 hours; remove the mold to obtain the hydrogel with added PEDOT:PSS.

[0123] Group 3, prepared according to Example 4.

[0124] In the ABTS test, the absorbance at 414nm of group 1, group 1, group 1 and the control group was measured with an enzyme marker at different reaction times. The lower the absorbance decreases with the reaction time, the better the overall antioxidant performance. The hydrogels of the three samples in the experimental group were soaked in deionized water until they swelled, and several hydrogel pieces of 5mm×5mm×1mm in the swelling equilibrium state were cut out. Each hydrogel piece was soaked in the ABTS aqueous solution with the same volume and height at 414nm absorbance of 1.8 to 2 for different times, and the absorbance of 200μL liquid at 414nm after the hydrogel pieces were taken out of each group at different reaction times was measured. The control group was only the same ABTS aqueous solution as the experimental group.

[0125] The CAT enzyme-like test uses a UV-visible spectrophotometer to measure the absorbance at 240nm of each experimental group and the control group under different reaction times. The lower the absorbance with reaction time, the better, which represents good catalase-like characteristics. The specific operation is to prepare a 50mM H2O2 solution as a working solution, add 500μL of the working solution to the control group, and use a UV-visible spectrophotometer to measure the absorbance of the control group at 240nm. If the absorbance is between 1.5-2.0, 500μL of the working solution can be added to each experimental group for the experiment. Otherwise, adjust the concentration of the H2O2 solution so that the absorbance of the control group at 240nm measured by the UV-visible spectrophotometer is between 1.5-2.0, and then add 500μL of the working solution to each experimental group for the experiment, and measure the absorbance of 200μL of the liquid at 240nm after taking out the hydrogel sheet from each group under different reaction times.

[0126] The GPx enzyme-like test uses a UV-visible spectrophotometer to measure the absorbance at 340 nm of each experimental group and the control group at different reaction times. The lower the absorbance with reaction time, the better, which represents good catalase-like properties. The specific operation is as follows: first, phosphate buffered saline (PBS) is used as a solvent to prepare a 50 mM glutathione (GSH) solution; then, a 4 mM nicotinamide adenine dinucleotide phosphate (NADPH) solution is prepared; then, a 10 mM hydrogen peroxide (H2O2) solution is prepared; finally, a glutathione reductase (GR) solution with a concentration of 17 U / mL is prepared. The above solutions are all materials in the kit. 370 μL PBS solution, 20 μL GSH, 50 μL NADPH solution, 50 μL GR solution and 10 μL H2O2 solution were used as the control group, 370 μL PBS solution, 20 μL GSH, 50 μL NADPH solution, 50 μL GR solution, 10 μL H2O2 solution and a 5 mm × 5 mm × 1 mm hydrogel piece immersed in PBS solution until swelling equilibrium were used as the sample group, and 500 μL working solution was added, 500 μL PBS solution and the three types of hydrogel pieces of 5 mm × 5 mm × 1 mm immersed in PBS solution until swelling equilibrium were used as the self group. First, use a UV-visible spectrophotometer to measure the absorbance of the control group at 340nm. If the absorbance is around 1.0, the experiment can be carried out. Otherwise, adjust the solution ratio of the control group so that the absorbance of the control group measured by the UV-visible spectrophotometer at 340nm is around 1. Then add 500μL of working solution to each experimental group and measure the absorbance of 200μL of liquid at 340nm after taking out the hydrogel sheet from each group at different reaction times.

[0127] Test result analysis:

[0128] For ABTS activity, Fig.11, the chart shows the performance of three hydrogel samples in the ABTS free radical scavenging experiment. Group 1 showed lower antioxidant capacity, while Group 2 showed slightly stronger antioxidant performance with a greater decrease in absorbance. Group 3 showed the best antioxidant performance, with a rapid and continuous decrease in absorbance, indicating that the nanozyme significantly enhanced the overall antioxidant effect of the hydrogel. This shows that nanozymes have potential advantages in improving the antioxidant capacity of materials.

[0129] For CAT-like activity, such as Fig.12 , showing the performance of three hydrogel samples in a simulated CAT activity test. Groups 1 and 2 showed a slight gradual decrease in absorbance, indicating a lower ability to decompose hydrogen peroxide. Group 3, on the other hand, showed a rapid and significant decrease in absorbance, indicating that these samples had extremely high CAT-like activity and could effectively decompose hydrogen peroxide. This enhanced activity may make these materials particularly valuable in applications that require rapid neutralization of oxidative stress.

[0130] For GPx-like activity, such as Fig.13 , Group 1 showed slight activity and a decrease in absorbance. Groups 2 and 3 showed a more obvious decrease in absorbance, especially Group 3, which showed the strongest GPx-like activity. This shows that the addition of nanozymes significantly enhanced the function of hydrogels to simulate natural GPx enzymes and efficiently degrade hydrogen peroxide. These results show that the introduction of nanozymes not only increases the antioxidant capacity of the material, but also effectively simulates the biological activity of GPx, providing an important basis for the development of new biocompatible materials.

[0131] Experimental Example 6

[0132] In vitro cytotoxicity assay

[0133] In the cytotoxicity experiment, HT-22 cells were first seeded on a 96-well culture plate and cultured in a 37°C, 5% CO2 incubator to 80%-90% confluence. 2 The nanozyme hydrogel prepared in Example 4 after intensive UV sterilization was immersed in complete culture medium for different time periods (6 hours, 12 hours, 24 hours and 48 hours) to prepare treated culture medium.

[0134] Next, HT-22 cells were treated with these culture media with different immersion times and incubated for 24 hours. After treatment, the survival rate of cells in each group was determined by CCK-8 method, and cell viability was evaluated by measuring the absorbance value.

[0135] Test result analysis:

[0136] Fig.14The effect of nanozyme hydrogel on the survival rate of HT-22 cells after soaking in complete culture medium for different time periods (6 hours, 12 hours, 24 hours and 48 hours) was demonstrated. The results showed that at these different soaking times, the cell survival rate was always close to 100%, with no significant change compared with the control group. This indicates that the soaking treatment of nanozyme hydrogel during these time periods has no obvious toxicity to HT-22 cells, and the cells can maintain a high survival rate.

[0137] Experimental Example 7

[0138] Study on the protective effect of nanozyme hydrogel on oxidative stress HT-22 cells

[0139] First, HT-22 cells were seeded on a culture plate and cultured in an incubator at 37°C and 5% CO2 to a confluence of 80%-90%. Subsequently, the cells were treated with H2O2 and LPS to induce oxidative stress, respectively.

[0140] Next, the 2 After strong UV disinfection, nanozyme hydrogel electrodes were immersed in complete culture medium for different time periods (6 hours, 12 hours and 24 hours). These treated culture media were used as drugs and added to HT-22 cells that had been exposed to oxidative stress conditions and incubated uniformly for 24 hours.

[0141] Finally, the CCK-8 method was used to determine the survival rate of cells in each group, and the cell viability was evaluated by measuring the absorbance value.

[0142] Test result analysis:

[0143] like Fig.15 and Fig.16 Compared with the group exposed only to H2O2 or LPS, the culture medium treated with nanozyme hydrogel electrodes was able to restore cell viability to a certain extent, indicating that nanozyme hydrogel electrodes can alleviate the damage of cells to a certain extent caused by oxidative stress caused by H2O2 or LPS.

[0144] This involves a highly compatible, non-invasive, semi-dry flexible electrode based on artificial enzymes. The electrode achieves low contact impedance and high mechanical strength with the skin through special chemical ratios and structural design. It is easy to operate and wear, has high antioxidant activity and multiple types of enzyme activity, and can collect EEG data for up to 10 hours.

[0145] Experiments have shown that the highly compatible non-invasive semi-dry flexible electrode based on nanozymes prepared in Examples 2 and 3 has similar sensitivity, robustness, and practicality in EEG experiments as those in Example 1.

[0146] Experiments have shown that the tensile and compressive resistance and biocompatibility of the nanozyme hydrogels prepared in Examples 5 and 6 are similar to those in Example 4.

Claims

1. A method for preparing a highly compatible non-invasive semi-dry flexible electrode based on nanozymes, characterized in that The following steps are involved: 1) Mixing a 5-10M hydrogen peroxide aqueous solution and a 98% concentrated sulfuric acid in a volume ratio of 3:5-8 in a container to obtain a mixed solution; immersing the conductive part of a universal silver chloride disc electrode of an electroencephalograph in the mixed solution for 10-20 minutes, taking it out, and washing it with deionized water; 2) soaking the conductive part of the electroencephalograph universal silver chloride disc electrode treated in step 1) in a silane aqueous solution for 6-8 hours; taking it out, washing it with deionized water and anhydrous ethanol in turn, and drying it in a nitrogen atmosphere for 2-5 hours; the silane aqueous solution is composed of 25%-30% 3-(isobutyleneoxy)propyltrimethoxysilane (TMSPMA), 2%-4% acetic acid, and the balance is deionized water by volume; 3) Prepare the prepolymer solution of nanozyme hydrogel: Add deionized water, polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 M1 nanozyme and glycerol are stirred evenly at a speed of 500-2000 rpm, ultrasonically degassed for 5-10 min, MBAA, APS and TEMED are added, and stirred at a speed of 500-2000 rpm for 1-2 min. The entire step 3) is protected from light to obtain a prepolymer solution of nanozyme hydrogel; The PEDOT:PSS is the abbreviation of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid; MBAA is the abbreviation of N,N'-methylenebisacrylamide; The APS is the abbreviation of ammonium persulfate; The TEMED is the abbreviation of tetramethylethylenediamine; The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 8%-20%; 1%-5%; 5%-25%; 0.05%-0.2%; 5%-15%; 0.01%-0.02%; 0.04%-0.2%; 0.1%-1%; deionized water is the balance; 4) Casting and curing: The conductive part of the electrode obtained in step 2) is arranged inside a mold with a notch on the side wall, and the insulated wire part of the electrode is passed through the notch and arranged outside the mold; the prepolymer solution of the nanozyme hydrogel obtained in step 3) is cast in the mold, and the ultraviolet light radiation intensity is 50-100 μW / cm 2 Irradiate for 15-60 minutes and let stand for 12-48 hours; remove the mold to obtain a highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes.

2. The preparation method according to claim 1, characterized in that The polyacrylamide, sodium alginate, PEDOT:PSS, Au 24 The mass percentages of M1 nanozyme, glycerol, MBAA, APS, TEMED and deionized water are: 12%, 2%, 10%, 0.05%, 10%, 0.017%, 0.043%; 0.6%; deionized water is the balance.

3. A highly compatible, non-invasive, semi-dry flexible electrode based on nanozymes prepared by the preparation method of claim 1 or 2.

Citation Information

Patent Citations

  • Clustering enzyme with atomic precision, preparation and application of clustering enzyme in nervous system diseases

    CN113827613A

  • Hydrogel electrode capable of being used for long-term non-invasive electroencephalogram collection and provided with conductive-substrate adhesion double layers and preparation method of hydrogel electrode

    CN116269404A

  • Semi-dry hydrogel electrode with antibacterial effect and preparation method thereof

    CN117814800A